Absorption difference between hepatotoxic pyrrolizidine alkaloids and their N-oxides – Mechanism and its potential toxic impact. (1st March 2020) - Yang, Mengbi; Ma, Jiang; Ruan, Jianqing; Zhang, Chunyuan; Ye, Yang; Pi-Cheng Fu, Peter; Lin, Ge
Abstract: Ethnopharmacological relevance: Pyrrolizidine alkaloids (PAs) are a group of phytotoxins widely present in about 3% of flowering plants. Many PA-containing herbal plants can cause liver injury. Our previous studies demonstrated that PA N -oxides are also hepatotoxic, with toxic potency much lower than the corresponding PAs, due to significant differences in their toxicokinetic fates. Aim of study: This study aimed to investigate the oral absorption of PAs and PA N -oxides for better understanding of their significant differences in toxicokinetics and toxic potency. Materials and methods: The oral absorption of PAs and PA N -oxides in rats and in rat in situ single pass intestine perfusion model was investigated. The intestinal permeability and absorption mechanisms of five pairs of PAs and PA N -oxides were evaluated by using Caco-2 monolayer model. Results: The plasma concentrations of total PAs and PA N -oxides within 0–60 min were significantly lower in rats orally treated with a PA N -oxide-containing herbal alkaloid extract than with a PA-containing herbal alkaloid extract at the same dose, indicating that the absorption of PA N -oxides was lower than that of PAs. Using the rat in situ single pass intestine perfusion model, less cumulative amounts of retrorsine N -oxide in mesenteric blood were observed compared to that of retrorsine. In Caco-2 monolayer model, all five PAs showed absorption with Papp AtoB values [(1.43–16.26) × 10 −6  cm/s] higher than those of corresponding N -oxides with Papp AtoB values lower than 1.35 × 10 −6  cm/s. A further mechanistic study demonstrated that except for senecionine N- oxide, retrorsine N- oxide, and lycopsamine N- oxide, all PAs and PA N -oxides investigated were absorbed via passive diffusion. While, for these 3 PA  N- oxides, in addition to passive diffusion as their primary transportation, efflux transporter-mediated active transportation was also involved but to a less extent with the efflux ratio of 2.31–3.41. Furthermore, a good correlation between lipophilicity and permeability of retronecine-type PAs and their N -oxides with absorption via passive diffusion was observed, demonstrating that PAs have a better oral absorbability than that of the corresponding PA N -oxides. Conclusion: We discovered that among many contributors, the lower intestinal absorption of PA N -oxides was the initiating contributor that caused differences in toxicokinetics and toxic potency between PAs and PA N -oxides. Graphical abstract: Image 1